KECERDASAN MAJEMUK HOWARD GARDNER DENGAN NILAI-NILAI ISLAM UNTUK MEMBENTUK KARAKTER ANAK MUSLIM - Siti Nur Laela; Titin Nurhidayati (PT. Sulthan Journal Publisher, 2025)
This study examines the conceptual framework for integrating Howard Gardner's theory of multiple intelligences with character education based on Islamic values. Gardner's theory highlights that individuals possess diverse and unique potential intelligences, comprising nine types: linguistic, logical-mathematical, spatial, bodily-kinesthetic, musical, interpersonal, intrapersonal, naturalistic, and existential. In contrast, Islamic education aims to cultivate individuals with noble character (akhlakul karimah). The research indicates that Gardner's intelligences can be developed through Islamic education as a means of instilling the values of monotheism, morality, and Sharia. The findings demonstrate that this integrated approach effectively produces Muslim children's cognitive intelligence alongside strong spiritual and moral development.